Penerapan Metode Grammar Translation untuk Baca-Tulis di MA As-Sunniyyah Jember - Ahmad Mizan Rosyadi; Muhammad Shokhibul Hidayah (Al-Fusha : Arabic Language Education Journal, 2022)
The lack of understanding of Arabic grammar as experienced by class XI D students at MA As-Sunniyyah makes students have weaknesses in analyzing and reading Arabic texts. This research aimed to describe the application of the grammar-translation method for class XI D at MA As-Sunniyyah through al-Jurūmiyyah book. This article used a qualitative approach with data collection through observation and documentation. The results of the research showed that the application of the grammar-translation method through the al-Jurūmiyyah book in class XI D MA As-Sunniyyah made students able to hone vocabulary preparation skills and identify iʻrāb through Arabic text reading with levels of 39% very capable, 39% able, and 22% less able. The grammar-translation method with the use of the al-Jurūmiyyah book in Arabic lessons can be used to hone students' skills in Arabic grammar.